The effects of SnO2 filler towards PVDF/SnO2 flexible piezoelectric nanogenerator performance / Habibah Zulkefle ... [et al.] - Zulkefle, Habibah; Abdul Halim, Mazliza; Awaludin, Nurul Huda; Kamaruzaman, Dayana; Md Sin, Nor Diyana; Sarip, Muhamad Naiman (UiTM Press, 2024)
The growing dependence on conventional electrical energy sources has resulted in significant degradation of the environment and increased costs. Renewable energy sources provide a promising option, but their actual implementation is hindered by several constraints. Alternative energy harvesting systems propose an innovative approach that involves real-time energy collecting from the surrounding, allowing for instantaneous use with temporary storage. This study utilized the Polyvinylidene Fluoride (PVDF) as an alternative energy harvester and the effect of SnO2 filler loading (1 wt%, 3 wt%, 5 wt%, 7 wt%, and 9 wt%) on the performance of PVDF flexible piezoelectric nanogenerators was investigated.